Increasing Anti Bullying Awareness of the Socialization Program at SDN 1 Manggungsari - Lutfiatul Khoiriyah; Usy Juana Putri (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This journal discusses the anti-bullying socialization program carried out by Walisongo State Islamic University KKN students at SDN 1 Manggungsari. The method used in this activity includes education through socialization to students and teachers of SD Negeri 1 Manggungsarı regarding Stop Bullying and its impact, as an effort to prevent bullying behavior, which was carried out on August 13, 2024, bullying in the school environment is a serious problem that can negatively affect the mental and physical health of students. This program aims to increase the awareness of students, teachers, and parents about the dangers of bullying and how to prevent it. Socialization activities are carried out through material delivery, discussion, and the use of audio-visual aids. The results of the activities show the enthusiasm of students in understanding and preventing bullying. To increase the effectiveness of the program, it is recommended that parents and counseling guidance teachers be involved in bullying prevention efforts